Analyzing the Effect of Bureaucratic Simplification Policy on Licensing Efficiency for Small and Medium Enterprises in Surabaya - Fadillah, Annisa Nur (Moccasin Journal De Public Perspective, 2025)
This study examines the impact of the bureaucratic simplification policy on licensing efficiency for Small and Medium Enterprises (SMEs) in Surabaya, Indonesia. SMEs play a crucial role in economic development but often face challenges due to complex and time-consuming licensing processes. In response, the Surabaya city government implemented a policy to streamline the licensing process and reduce administrative burdens. Using a mixed-methods approach, this research combines quantitative analysis of processing time, ease of access, and satisfaction levels before and after the policy implementation, along with qualitative insights from interviews and Focus Group Discussions (FGDs) with SMEs and government officials. The findings show that the policy resulted in a significant reduction in licensing processing time (38.2%), improved ease of access (45.2%), and a substantial increase in satisfaction (46.4%). Regression analysis reveals that policy implementation and training for government officials are the primary drivers of these improvements, while technological infrastructure plays a secondary role. Qualitative feedback corroborates these findings, highlighting enhanced government efficiency, greater transparency, and improved SME satisfaction. However, challenges related to digital literacy among SMEs were also identified, suggesting a need for ongoing support. Overall, the study demonstrates that bureaucratic simplification has positively impacted licensing efficiency, with implications for broader regulatory reforms aimed at supporting SME growth.